Governing a collective bad: Social learning in the management of crop diseases - Damtew, Elias; Mierlo, B. van; Lie, R.; Struik, P.C.; Leeuwis, Cees; Lemaga, B.; Smart, C.D. (Springer, 2020)
There has been strong research interest in designing and testing learning approaches for enhancing and sustaining the capacity of communities to manage collective action problems. Broadening the perspective from well-known social learning approaches in natural resource management, this study explores how social learning as a communicative process influences collective action in contagious crop disease management. A series of facilitated discussion and reflection sessions about late blight management created the social learning space for potato farmers in Ethiopia. Communicative utterances of participants in the sessions served as the units of analysis. The study demonstrates how and to what extent social learning, in the form of aligned new knowledge, relations and actions occurred and formed the basis for collective action in the management of late blight.